Mechanism of acetate synthesis from CO2 by Clostridium acidiurici. - Waber, L J (1979)
Total synthesis of acetate from CO2 by Clostridium acidiurici during fermentations of hypoxanthine has been shown to involve synthesis of glycine from methylenetetrahydrofolate, CO2, and NH3. The glycine is converted to serine by the addition of methylenetetrahydrofolate, and the resulting serine is converted to pyruvate, which is decarboxylated to form acetate. Since CO2 is converted to methylenetetrahydrofolate, both carbons of the acetate are derived from CO2. The evidence supporting this pathway is based on (i) the demonstration that glycine decarboxylase is present in C. acidiurici, (ii) the fact that glycine is synthesized by crude extracts at a rate which is rapid enough to account for the in vivo synthesis of acetate from CO2, (iii) the fact that methylenetetrahydrofolate is an intermediate in the formation of both carbons of acetate from CO2, and (iv) the fact that the alpha carbon of glycine is the source of the carboxyl group of acetate. Evidence is presented that this synthesis of acetate does not involve carboxylation of a methyl corrinoid enzyme such as occurs in Clostridium thermoaceticum and Clostridium formicoaceticum. Thus, there are two different mechanisms for the total synthesis of acetate from CO2 by clostridia.